Preventing Double Spending Attacks through Crow Search Algorithm to Enhance E-Voting System Security - Muthulakshmi, S; Kannammal, A (EAI Endorsed Transactions on Internet of Things, 2024)
Electronic voting system is the process of polling votes and counting votes. In most of the countries voting may now be done electronically, there are still several difficulties involved, including the expense of paper, how ballots are organized, the possibility of varying results when tallying the votes, and others. Duplicate votes pose a significant concern as they can be fraudulently cast by individuals. To focus on this issue, Distributed Ledger Technology (DLT) is employed to enhance the voting procedure in a secured manner. A directed acyclic graph is used by the Internet of Things Application (IOTA), a promising distributed ledger system. Faster transaction confirmation, high scalability and zero transaction fees are achieved via the Directed Acyclic Graph structure. In both IOTA tangle and blockchain technology, the public cast duplicate votes. The unauthorized user can create duplicate votes in the blockchain as well as IOTA tangle. This can be focused in this proposed method. The double spending problem can be solved by using Crow Search Algorithm (CSA). This Optimization problem produces an improved result for resolving double spending in e-voting systems.
Keywords: Internet of Things Application; Tangle; Directed Acrylic Graph; Crow Search Algorithm; E-Voting System; Double Spending Attack